The Concept of Humanity in the Study of Islamic and Western Educational Philosophy - Sumarno, Sumarno; Musfiratul, Indah; Syaifulloh, Imam (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
This study focuses on the concept of humanity in Islamic and Western educational philosophy, which plays a pivotal role in shaping educational systems and character development. In Islamic education, humans are viewed as beings endowed with fitrah—an innate disposition to recognize God and fulfill their purpose as stewards on earth, striving towards insan kamil (the perfect human). Conversely, Western educational philosophy emphasizes rationality and individual freedom. This research aims to identify the similarities and differences between the two perspectives and explore the potential integration of their values to create a holistic educational system. This study employs a qualitative approach through a literature review (library research). Data were gathered through critical analysis of primary and secondary sources, including works by figures such as Al-Ghazali, Ibn Sina, Kant, and Dewey. A comparative approach was utilized to analyze the characteristics of each educational philosophy. The study reveals that Islamic and Western educational philosophies have differing paradigms but complement each other. Islamic education emphasizes the integration of spiritual, intellectual, and moral aspects through the concepts of fitrah and tawhid. On the other hand, Western education prioritizes individual freedom and the development of rationality. Despite fundamental differences, the two approaches can be integrated to form a more holistic educational system encompassing spiritual, moral, and rational values. This research contributes to the development of cross-cultural and interfaith educational theories. However, it is limited to a literature-based study without empirical validation. Further research with an empirical approach is necessary to test the implementation of Islamic and Western value integration in educational systems. This study offers a novel perspective on the potential integration of spiritual and rational values in building a holistic educational system, which is essential in addressing global educational challenges that require multidimensional approaches to character development.